Clinical Usefulness of Cell-based Indirect Immunofluorescence Assay for the Detection of Aquaporin-4 Antibodies in Neuromyelitis Optica Spectrum Disorder - Kang, Eun-suk (The Korean Society for Laboratory Medicine, 2012)
BACKGROUND: The presence of antibodies to aquaporin-4 (AQP4) has been identified as a key characteristic of neuromyelitis optica spectrum disorder (NMOSD), an autoimmune inflammatory demyelinating central nervous system (CNS) disorder. We evaluated the performance of a cell-based indirect immunofluorescence assay (CIIFA) for detecting AQP4 antibodies using antigen prepared with a recombinant AQP4 peptide transfection technique and assessed the usefulness of CIIFA for diagnosis of NMOSD in routine clinical practice. METHODS: Forty-six serum samples from 36 patients as a comparison set and another 101 patients enrolled consecutively from a neurology clinic were included. CIIFA and fluorescence immunoprecipitation assays (FIPA) were performed. CIIFA was performed at 2 different institutions for comparison purposes. RESULTS: CIIFA and FIPA sensitivity in the comparison set was 86% and 79% in neuromyelitis optica (NMO) patients and 55% and 36% in high-risk NMO patients, respectively. The semiquantitative titer measured by CIIFA correlated well with the arbitrary unit (fluorescence units [FU]) derived from FIPA (r=0.66). Titers measured by CIIFA and FIPA were elevated in NMO patients compared to high-risk NMO patients (1:240 vs. 1:180 and 8,390 vs. 4,059 FU, respectively). The frequency of AQP4 antibody detection by CIIFA in 101 consecutively enrolled patients was 100% in NMO and 23% in high-risk NMO patients, while only 4.6% in control patients, including those with multiple sclerosis. CONCLUSIONS: Detection of AQP4 antibodies by CIIFA provides sensitive and highly specific diagnostic information for NMO and high-risk NMO patients, which can be used to differentiate these conditions from other demyelinating CNS diseases.